Musculoskeletal Infection in Orthopaedic Trauma: Assessment of the 2018 International Consensus Meeting on Musculoskeletal Infection. (20th May 2020) - Obremskey, William T.; Metsemakers, Willem-Jan; Schlatterer, Daniel R.; Tetsworth, Kevin; Egol, Kenneth; Kates, Stephen; McNally, Martin; Gibbons, John; Kenny, Paddy; Obremskey, William T.; Stangl, Paul; Patzakis, Michael J.; et al.
Abstract : Abstract: Fracture-related infections (FRIs) are among the most common complications following fracture fixation, and they have a huge economic and functional impact on patients. Because consensus guidelines with respect to prevention, diagnosis, and treatment of this major complication are scarce, delegates from different countries gathered in Philadelphia in July 2018 as part of the Second International Consensus Meeting (ICM) on Musculoskeletal Infection. This paper summarizes the discussion and recommendations from that consensus meeting, using the Delphi technique, with a focus on FRIs. A standardized definition that was based on diagnostic criteria was endorsed, which will hopefully improve reporting and research on FRIs in the future. Furthermore, this paper provides a grade of evidence (strong, moderate, limited, or consensus) for strategies and practices that prevent and treat infection. The grade of evidence is based on the quality of evidence as utilized by the American Academy of Orthopaedic Surgeons. The guidelines presented herein focus not only on the appropriate use of antibiotics, but also on practices for the timing of fracture fixation, soft-tissue coverage, and bone defect and hardware management. We hope that this summary as well as the full document by the International Consensus Group are utilized by those who are charged with musculoskeletal care internationally to optimize their management strategies for the prevention and treatment of FRIs.